Manajemen Kurikulum Praktik Kerja Lapangan Berorientasi Dunia Usaha Dan Dunia Industri Di Smk Negeri 2 Purwodadi - Jaenur, Jaenur, Prof.Dr. Sutama, M.Pd (2017)
Jaenur. Q 100 15 0027. Curriculum Management Practices Field Work Oriented Business and Industry at SMK Negeri2 Purwodadi. Thesis. Pascasarjana Universitas Muhammadiyah Surakarta 2017. The purpose of this research there are three 1) Describe the practice of curriculum planning and industry oriented businesses in SMK Negeri 2 Purwodadi, 2) Describe the implementation of the technical curriculum in business and industry oriented in SMK Negeri 2 Purwodadi, 3) Describes the practice of business evaluation of curriculum-oriented work and industry in SMK Negeri 2 Purwodadi. Data collection techniques of observation, interviews and documentation. test the validity of using triangulation. Data were analyzed using interactive data, data reduction, data presentation, and conclusion. The results of this study there are three. 1) Curriculum applied in SMK Negeri 2 Purwodadi in organizing job training is the curriculum SMK Negeri 2 Purwodadi in the academic year 2016/2017. Activities undertaken during the planning phase of curriculum SMK Negeri 2 Purwodadi include: (a) forming a team of curriculum developers (TPK), (b) mapping industry through meetings or IHT, (c) curriculum, (d) validation and revision, (e) curriculum finalization (f) debriefing participants PKL, (g) the establishment of a mentor, and h) evaluation (. 2)Implementation of the activities of street vendors in SMK Negeri 2 Purwodadi performed by students of class XII. PKL activity system implementation using block models relase for three months. During the activities of street vendors, learning entirely done by DU / DI spouse / Industry. Activities undertaken by learners among others following study in DU / DI, completing tasks or jobs given by DU / DI, filling journals prepared a report on activities of street vendors and street vendors. This journal is made complete as possible in accordance with the learning material / type of work and other tasks given industry mentor and record important events (the learning experience) over the activities of street vendors in DU / DI. 3) evaluation of the business world diterap Kandala street vendors and industry oriented curriculum at SMK Negeri 2 Purwodadi is the measurement of the achievement of learner performance that includes technical and non technical aspects. Participants PKL achievement of performance stated in the certificate of assessment. PesertaPKL performance assessment conducted by DU / DI couples where learners do the street vendors and the school guidance counselor in a written report on all activities of street vendors. Each participant PKL eligible activities awarded certificates by DU / DI. This certificate can be used as a statement indicating that such learners have gained work experience in the corporate world or the world industry. Keywords: curriculum management, employment practices industry, business world and the industrial world